Correction: TDRD6 mediates early steps of spliceosome maturation in primary spermatocytes. - Müge Akpınar; Mathias Lesche; Grigorios Fanourgakis; Jun Fu; Konstantinos Anastassiadis; Andreas Dahl; Rolf Jessberger (PLoS Genetics)
[This corrects the article DOI: 10.1371/journal.pgen.1006660.].